Food Chain in the Sea-Its Values, Challenges and Prospects. - Lokman Shamsudin, (2000)
The planet world had a population of 4 billion in the year 1975, since than its population is ever increasing at a tremendous rate and by the year 2025 it is estimated to reach 8 billion. The land usage on the earth surface is almost exhausted while its arid coverage is ca 43.5% of the earth surface. As such, human being has no alternative but inevitably has to go to the sea which covers > 75% of the earth surface, for food source in the near future.